Diamond Detectors for Radiotherapy X-Ray Small Beam Dosimetry - Talamonti, C.; Kanxheri, K.; Pallotta, S.; Servoli, L. (Frontiers in Physics, 2021)
In the last years, many X-Ray treatment machines using small and/or non-standard radiation fields have been introduced in radiotherapy clinical routine. The introduction of these new treatment modalities has led to the development of high conformal radiotherapy treatment techniques. When using these treating techniques patients are exposed to non-uniform radiation fields, high dose gradients, time and space variation of dose rates and beam energy spectrum, making more demanding to reach the required degree of accuracy in clinical dosimetry. Continuing to use standard field procedures and detectors, will generate a reduced accuracy of clinical dosimetry, running the risk to overshadow the progress made so far in radiotherapy applications. These dosimetric issues represent a new challenge for medical physicists. To choose the most appropriate detector for small field dosimetry, a compromise between different features is necessary. Short and long term stability, linear response to the absorbeddose and dose rate, no energy and angular dependence, are all needed but not sufficient. The two most sought attributes for small field dosimetry are water equivalence and spatial resolution. If the detector is not small enough, the dosimetric measurements will be strongly affected by the perturbation of the charged particle fluence due to the detector size because the CPE condition is seldom fulfilled. Hence in order to minimize the averaging effect for non-uniform radiation fields, small dimensions and high sensitivity are required characteristics. No dosimeter is currently fulfilling all requirements, but diamond properties, seem promising and could lead to a marked improvement. Diamond has long been used as material for dosimeters, but only in the 80s natural diamond was used for medical applications. The availability of reproducible synthetic diamonds at a lower cost compared to the natural ones made possible the diffusion of diamond in dosimetry. This paper aims to review the use of synthetic poly and single-crystal diamond dosimeters in radiotherapy, focusing on their performance under small MegaVoltage photon beams. Both commercial and prototype diamond dosimeters behaviour are described and analysed.